Langmuir and langmuir-blodgett films of polyfluorenes and their use in polymer light-emitting diodes - Ferreira, Marystela; Olivati, Clarissa A.; Machado, Angelita M.; Assaka, Andressa M.; Giacometti, Jose A.; Akcelrud, Leni; Oliveira, Osvaldo N. (Springer, 2007)
The Langmuir and Langmuir-Blodgett (LB) film properties of two polyfluorene derivatives, namely poly(2,7-9,9'-dihexylfluorene-dyil) (PDHF) and poly(9,9 dihexylfluorene-dyil-vynilene-alt-1,4-phenylene-vyninele) (PDHF-PV), are reported. Surface pressure (Pi-A) and surface potential (Delta V-A) isotherms indicated that PDHF-PV forms true monolayers at the air/water interface, but PDHF does not. LB films could be transferred onto various types of substrate for both PDHF and PDHF-PV. Only the LB films from PDHF-PV could withstand deposition of a layer of evaporated metal to form a light-emitting diode (PLED), which had typical rectifying characteristics and emitted blue light. It is inferred that the ability of the polymer to form true monomolecular layers at the air/water interface seems to be associated with the viability of the LB films in PLEDs.
Keywords: Langmuir films; LB films; polyfluorene derivatives; PLED; photoluminesce; electroluminescence